Novel therapies for proliferative retinopathies - Juan Manuel Martinez-Alejo; Leopoldo Martin Baiza-Duran; Juan de Dios Quintana-Hau (SAGE Publishing, 2022)
Proliferative retinopathies, such as neovascular age-related macular degeneration and proliferative diabetic retinopathy, are a special health issue due to their contribution to irreversible blindness. Although the promoting conditions and physiopathology of proliferative retinopathies are different, these feature a highly detrimental angiogenesis driven by the overproduction of vascular endothelial growth factor (VEGF). This article describes the mechanism of action of ocular antiangiogenic therapies currently found in clinical development. Systems classify accordingly as (a) novel anti-VEGF systems, (b) molecules targeting non-VEGF pathways, and (c) gene therapies. Whereas most therapies are designed to neutralize VEGF, there is a significant set of products with diverse complexity and mechanism of action. Anti-VEGF therapies are still the most studied approach to tackle angiogenesis. Therapies targeting non-VEGF pathways, however, are highlighted because they could be an option for patients nonresponsive to anti-VEGF therapies. Finally, gene therapy is a promissory technology platform but still is subject to demonstrate safety and efficacy.